Localism, Landscape, and the Ambiguities of Place : German-Speaking Central Europe, 1860-1930. - Blackbourn, David (German and European studies., 2014)
These essays do not assume the primacy of national allegiance. Instead, by using the 'sense of place' as a prism to look at German identity in new ways, they examine a sense of 'Germanness' that was neither self-evident nor unchanging.